Religious Nationalism as Solution in the Chaotic Social, Economics and the Business Reality - Yogi Simhanath (International Journal of Religious and Cultural Studies, 2020)
The purpose of this article is to highlight the importance of religious nationalism to protect vital national interests, maintain stability and preservation of core values. The expression of the constitution of Indonesia is a guarantor in integrating the people from all groups and strata of Indonesian society. It ensures a favorable internal and external condition. Religious nationalism is super glue that bonds the people, religions and the nation as a single entity. This is still utmost relevant in the pandemic.